Analyzing the obsession of the main character in short story: Young Goodman Brown - Nabiela DRahmah (Jurnal Penelitian Humaniora, 2021)
This study was aimed to identify how the main character is depicted and identify the characteristics presented by Nathaniel Hawthrone in the short story Young Goodman Brown. This research used a qualitative descriptive method to analyze the data. The primary data were the quotes and the sentences that describe the characters and obsession characteristics of the main characters in Young Goodman Brown’s short story. The authors analyzed several trusted journals, articles, and internet sources to conduct a more detailed analysis. The results show that the author of this short story takes the theme of religion, mystery, personal stories and implies moral education. The protagonist, Goodman Brown, is a man who tries to find his way in life. The analysis of this short story finds Young Goodman Brown’s obsession with getting to know the demonic sect. Based on the analysis of the personality structure consisting of the id, ego, and superego. The character has a balance of personality. The analysis of the clarification of emotions shows that the main characters are doubt, fear, anger, sadness, and disappointment.